Arsenic trioxide encapsulated liposomes prepared via copper acetate gradient loading method and its antitumor efficiency - Shaoning Wang; Chunxiu Liu; Cunyang Wang; Jia Ma; Hui Xu; Jianbo Guo; Yihui Deng (Elsevier, 2020)
In this study, arsenic trioxide (ATO) was encapsulated in liposomes via copper acetate (Cu(OAc)2) gradients and high entrapment efficiency of over 80% was obtained. The average particle size and the zeta-potential of the liposomes were detected to be 115.1 ± 29.1 nm and −21.97 ± 0.6 mV, respectively. The TEM images showed rod-like precipitates in the inner aqueous phase, which was supposed be due to the formation of insoluble ATOCu complex. The in vitro drug release of ATOCu liposomes exhibited a sustained release over 72 h, and the release rates decreased with the increase of the pH of release media. Pharmacokinetic and tissue distribution studies of ATO liposomes showed significantly reduced plasma clearance rate, increased AUC0-12h and T1/2, and improved tumor distribution of As compared to iv administration of ATO solution. The anti-tumor effect of ATO loaded liposomes to S180 tumor-bearing mice was significantly improved with a tumor inhibition rate of 61.2%, meanwhile the toxicity of encapsulated ATO was greatly decreased. In conclusion, ATO can be effectively encapsulated into liposomes by remote loading method via Cu(OAc)2 gradients; the co-administration of ATO and Cu(II) via liposomal formulation may find wide applications in the treatment of various tumors.